Consumer trust in the tampon market in regards to health - Placenti, Apolline; Tocquer, Gerard A.; Ransom, Lakeesha K.; Vimolwan Yukongdi; EDHEC Business School, France; Asian Institute of Technology (2021)
Unlike other segments of the menstrual products market, the tampon market has shown some weakness in the past few years, especially in the more mature markets in developed countries, where scandals around the safety of tampons burst. This master research aims at studying the trust consumers put in the tampon industry, whether this trust is really lacking, explore reasons why that might be and offer some insights to help tampon brands to regain the trust they lost, focusing on the health aspect of the trust. This study defined consumer trust and CSR, and explored why it was crucial for businesses to focus on customer retention. We then linked CSR and customer retention, trust, and the importance of word-of-mouth, whether offline or online, in the construction of brand perception for consumers. This was completed by an overview of the menstrual product markets, especially the tampon market and its challenges. It enabled to determine that most of the alleged mistrust actually comes from misconceptions on the tampon industry. This helped design the survey used to test our hypothesis that there was a lack of trust from consumers, why there was one and how to regain that trust. This study found that there was indeed a deep lack of trust from women in the tampon industry, especially in the health aspect of the product. Women are distrustful of tampons when it comes to the ingredients used to make them, their risk of contracting toxic shock syndrome and intimate infections, and hygiene. Overall, women believe that tampon brands do not communicate nor act enough on the risks related to the use of their products, but would be willing to trust brands again if they were to communicate, and especially act more. The study then gives insights on what channels are best to use in order to right the misconceptions that led to the lack of trust from consumers.
A research submitted in partial fulfillment of the requirements for the degree of Master of Business Administration
Research Studies Project Report (M.B.A.) - Asian Institute of Technology, 2021
Keywords: Tampons; Consumer behavior; Corporate social responsibility series